Effects of Experimental Configuration on the Morphology of Two-Dimensional ZnO Nanostructures Synthesized by Thermal Chemical-Vapor Deposition - Seok Cheol Choi (Crystals, 2020)
Using two experimental configurations, self-assembled zinc oxide (ZnO) nanostructures including nanoplates, nanosaws, and nanobelts were synthesized by thermal chemical-vapor deposition (CVD), and their morphological properties were investigated. ZnO nanostructures grown on Au-coated Si substrates in a parallel setup revealed highly defined ZnO nanoplates and branched nanowires. ZnO nanostructures grown in a perpendicular setup using Si substrates with and without the Au catalyst exhibited vertically oriented ZnO nanosaws and randomly aligned nanobelts, respectively. In the thermal CVD method, experiment conditions such as oxygen-flow rate, growth temperature, and catalyst, and experimental configurations (i.e., parallel and perpendicular setups) were important parameters to control the morphologies of two-dimensional ZnO nanostructures showing platelike, sawlike, and beltlike shapes.